Efficient Queue Management System for Rumah Sehat Dokter Zoji Clinic in Cianjur - Palupi, Irma; Khairi, Muhammad Daffa; Wahyudi, Bambang Ari (Jurnal Abdimas, 2025)
This charity project aims to implement an efficient queue management system for Rumah Sehat Dokter Zoji Clinic, located in Cianjur, Indonesia. The clinic, known for its alternative and affordable healthcare services using a "pay as you wish" model, experiences high patient volumes—ranging from 300 to 500 daily on weekdays and up to 1,000 on Sundays. To address the growing demand and improve patient care, a mobile application was developed using Flutter with Firebase as the database to organize patient data and manage queue schedules effectively. The system prioritizes patients based on the severity of their conditions, categorizing them into Emergency, Severe, Moderate, and Mild levels. This prioritization ensures that those in urgent need receive prompt care, while others are integrated into the regular queue accordingly. The project also focuses on educating clinic staff and patients about the new system, recognizing varying levels of familiarity with technology. A hybrid approach to the queue system remains in place, accommodating those who prefer traditional methods. The implementation of this system is expected to streamline operations at the clinic, enhancing the overall efficiency and effectiveness of patient care delivery.